Komunikasi Emosional Berbasis Makna dalam Lirik Lagu “Gala Bunga Matahari” Karya Sal Priadi - Callysta Angelyn Wijaya; Farid Rusdi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
Music is a communication medium capable of conveying messages and emotions through signs, figurative language, and symbols that influence the audience's interpretation. The song